Multi‐objective operation of distributed generations and thermal blocks in microgrids based on energy management system - Homayoun, Rohollah; Bahmani‐Firouzi, Bahman; Niknam, Taher (IET generation, transmission & distribution, 2021)
The optimal multi‐objective operation of microgrids with distributed generations and thermal block based on the energy management system is presented. In the thermal block, the combined heat and power system and boiler and thermal storage system supply the load of the block thermal. Therefore, the proposed strategy minimises three objectives of an microgrid's operation, that is, cost, energy loss and voltage deviation functions. Also, it is subject to AC power flow equations, system operation limits and distributed generations and thermal block constraints. The problem is modelled as a multi‐objective optimisation method; then is converted to a single‐objective problem model using the ε‐constraint‐based Pareto optimisation. Moreover, the proposed strategy includes uncertainties of the load, energy price and active power of renewable distributed generations; hence, a stochastic programming based on the hybrid Mont Carlo simulation and point estimate method is used to model these uncertain parameters. Then, the teaching–learning‐based optimisation and firefly algorithm are utilised to solve the problem to achieve a reliable optimal solution. Finally, the proposed strategy is simulated on the IEEE 69‐bus microgrid, and thus, the capabilities of the proposed strategy are extracted.